Proteome characterisation of extracellular vesicles isolated from heart. Issue 13 (6th May 2021) - Claridge, Bethany; Rai, Alin; Fang, Haoyun; Matsumoto, Aya; Luo, Jieting; McMullen, Julie R.; Greening, David W.
Abstract: Cardiac intercellular communication is critical for heart function and often dysregulated in cardiovascular diseases. While cardiac extracellular vesicles (cEVs) are emerging mediators of signalling, their isolation remains a technical challenge hindering our understanding of cEV protein composition. Here, we utilised Langendorff‐collagenase‐based enzymatic perfusion and differential centrifugation to isolate cEVs from mouse heart (yield 3–6 μg/heart). cEVs are ∼200 nm, express classical EV markers (Cd63/81/9 +, Tsg101 +, Pdcd6ip/Alix + ), and are depleted of blood (Alb/Fga/Hba) and cardiac damage markers (Mb, Tnnt2, Ldhb). Comparison with mechanically‐derived EVs revealed greater detection of EV markers and decreased cardiac damage contaminants. Mass spectrometry‐based proteomic profiling revealed 1721 proteins in cEVs, implicated in proteasomal and autophagic proteostasis, glycolysis, and fatty acid metabolism; essential functions often disrupted in cardiac pathologies. There was striking enrichment of 942 proteins in cEVs compared to mouse heart tissue ‐ implicated in EV biogenesis, antioxidant activity, and lipid transport, suggesting active cargo selection and specialised function. Interestingly, cEVs contain marker proteins for cardiomyocytes, cardiac progenitors, B‐cells, T‐cells, macrophages, smooth muscle cells, endothelial cells, and cardiac fibroblasts, suggesting diverse cellular origin. We present a method of cEV isolation and provide insight into potential functions, enabling future studies into EV roles in cardiac physiology and disease.